2020
DOI: 10.1038/s41398-020-0761-6
|View full text |Cite
|
Sign up to set email alerts
|

Parental and social factors in relation to child psychopathology, behavior, and cognitive function

Abstract: Parental and social factors have long-term impact on the neurodevelopment of offspring, but tend to highly covary with each other. Thus, it is difficult to parse out which parental and social factor contributes most to neurodevelopmental outcomes. This study aimed to assess clusters of parental and social factors associated with child psychopathology, behavioral problems, and cognition. This study employed the data of 11,875 children (9 to 11 years) from the Adolescent Brain Cognitive Development (ABCD) study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…Moreover, a father’s education matters for the child’s anemia status, WPPSI, and prosocial scores. This is congruent with previous findings, suggesting that lower socioeconomic status is linked with lower IQ and executive functions [ 31 , 32 ]. Similarly, consistent with previous findings [ 33 , 34 ], our study identified that parenting style, which is low in demands and responsiveness, is linked with poor cognitive and prosocial abilities.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, a father’s education matters for the child’s anemia status, WPPSI, and prosocial scores. This is congruent with previous findings, suggesting that lower socioeconomic status is linked with lower IQ and executive functions [ 31 , 32 ]. Similarly, consistent with previous findings [ 33 , 34 ], our study identified that parenting style, which is low in demands and responsiveness, is linked with poor cognitive and prosocial abilities.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, GM-BHQ was more strongly correlated with cognitive function than its regional subscales including hippocampus-BHQ or parahippocampus-BHQ (Watanabe et al, 2021), indicating that the whole-brain GMV reflects cognitive function better than individual regional GMV. As the whole-brain GMV is influenced by one's personality, cognitive ability, and surrounding environment (Kokubun & Yamakawa, 2019;Kokubun et al, 2018Kokubun et al, , 2020Kokubun et al, , 2021Nemoto et al, 2017;Watanabe et al, 2021), it has been shown that motivation (Subramanian et al, 2020;Włodarska et al, 2019;Zhang et al, 2020) and empathy (Jami et al, 2021;Putrino et al, 2021) are also influenced by those factors. Therefore, it is reasonable to hypothesize that whole-brain GMV correlates with motivation and empathy.…”
Section: Relationship Between Motivation and Brainmentioning
confidence: 99%
“…It is interesting to compare the findings of Lees et al with recently published results from the same ABCD cohort using a data-driven principal component analysis of 39 environmental measures and 30 child behavior and cognitive measures to identify clusters of parental and social factors and clusters of child outcomes (16). Maternal alcohol use was not associated with any child psychopathology, behavioral, or cognitive outcomes.…”
mentioning
confidence: 89%
“…These findings align with converging evidence among studies of the developmental origins of health and disease for the transmission of maternal psychological distress to offspring, perpetuated by exposure to less optimal caregiving and an adverse postnatal environment experienced in the context of parental stress and psychopathology (4). Although Lees et al adjusted for maternal depression in their primary analyses, demographically matched samples were not matched on maternal depression and other social, parental, and environmental factors that were most strongly associated with child psychopathology in Zhang et al (16). Taken together, these two studies from the ABCD cohort pose a core conceptual challenge in integrating behavioral teratology studies with the developmental origins of health and disease and other research approaches-are we interested in asking what harm might alcohol cause, or what predicts poorer (or enhanced) development?…”
mentioning
confidence: 99%